Wifredo Lam the imagination at work - Cabañas, Kaira Marie 1974-; Alberro, Alexander 1957-; Chang, Alexandra 1988-; Noel, Samantha ca. 20./21.Jh; Lacaze Mohrmann, Maichaëla de; Hickey, Andria (Pace, 2022)
Foreword / Alexander Alberro -- Essays: Circa 1940: animating intimate relations / Kaira M. Cabañas -- Searching for Wifredo Lam: reclaiming, identities, and context / Alexandra Chang -- The poetics of black-Cuban sovereignty in Wifredo Lam's art / Samantha A. Noël -- Selected paintings -- Selected sculptures -- Lam's crossings and critical positions: a chronology / Michaëla de Lacaze Mohrmann -- List of works -- Afterword / Andria Hickey.
"Published on occasion of Wifredo Lam: The Imagination at Work, November 10-December 18, 2021 ... Pace Galley, ... New York"--Colophon
Keywords: Lam, Wifredo -- 1902-1982; Geschichte 1926-1977; Bronzeplastik; Malerei; Lam, Wifredo / Exhibitions; Ausstellungskatalog -- Pace Gallery -- 10.11.2021-18.12.2021 -- New York, NY; Bildband